The Emerging Fungal Pathogen Candida auris Induces IFNγ to Colonize the Skin. - Diprasom Das; Shrihari M Ganesh; Abtar Mishra; Mihai G Netea; Shankar Thangamani (PLoS Pathogens)
Candida auris is an emerging multidrug-resistant skin-tropic fungal pathogen that causes serious human infections. However, the factors that regulate C. auris skin infection in vivo are still unclear. In this study, we identified that, unlike Candida albicans, which induces IL-17-secreting protective effector Th17 cells, C. auris predominately induces IFNγ-secreting pathogenic Th1 cells during reinfection. Surprisingly, we found that IFNγ enhances skin infection of C. auris but not C. albicans. Mechanistically, IFNγ enhances skin infection of C. auris by dampening the protective IL-17 responses and increasing dermal damage. Furthermore, we identified that the development of Th1 cells occurs through IL-12, produced by C. auris-induced inflammatory macrophages and monocyte-derived dendritic cells. In addition, our findings reveal that C. auris unique cell wall outer mannan layer regulates the development of Th1 and Th17 cells. Collectively, our findings, for the first time, identified that C. auris induces IFNγ to persist in the skin. These findings help explain why C. auris but not C. albicans preferentially persist in the skin long-term, with the potential to identify novel therapeutic approaches to prevent and treat this emerging fungal pathogen in humans.